Rethinking class: culture, identities and lifestyle - Devine, Fiona; Savage, Mike; Scott, John; Crompton, Rosemary (Palgrave Macmillan, 2005)
Edited by leading British sociologists of stratification, this book advances contemporary debates in class analysis. It draws on current theoretical debates in sociology and considers the implications of the cultural turn for the study of class. It brings together the very latest empirical work on contemporary topics such as culture, identities and lifestyles undertaken by researchers from Britain, Germany, the Netherlands and Australia. It will be required reading for those committed to pushing the boundaries of class and stratification in new and exciting directions around the world.